Pragmatik dalam Al-Qur’an: Analisis Tindak Tutur Lokusi, Ilokusi dan Perlokusi Pada Tafsir Ayat-Ayat Hukum - Fadila Ikke Nuralita (Studia Quranika, 2024)
The Qur'an is a holy book that uses various variations of language styles in conveying messages both with narrative, argumentative, dialog-interactive patterns and stories so as to bring important teachings for humans throughout the ages in the midst of the use of language in the midst of daily life in the form of speech acts are not limited in number. This article aim to pragmatics in the Qur'an by analyzing in depth the speech acts of locution, illocution and perlocution of legal verses. The primary data source of this research is the verses of law in the Qur'an using qualitative research design with literature research method. The data is collected through the themes of the Qur'anic verses about law and analyzed by using Austin's theory with locution, illocution and perlocutionary speech acts. The results of the study found the use of pragmatics in the Qur'an with the theme of law. The analysis of pragmatics or speech acts is needed by the community in order to understand deeply related to the implied and implied meaning in the verses of the Qur'an